Nuove considerazioni sul pregiudizio nei confronti della disabilità - Fratini, Tommaso (Studi sulla Formazione/Open Journal of Education, 2016)
This article addresses the theme of prejudice in relation to disability as a central aspect in the context of the issue of social exclusion in people with disabilities. Going beyond the analysis of prejudice in narrow cognitive terms, as a form of stereotype, its conceptualization presents itself as a result of pathological defense mechanisms. With this in mind, prejudice towards disability is re-read in light of massive defenses against not only diversity, but also against those who carry mental pain. The articles concludes with a reflection on the ways in which prejudice against disability can be fought in our society in order to promote genuine social change.